The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fdigh.2017.00004
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Decisions and Unbalanced Power. How Latin Cities Shaped Their Terrestrial Transportation Network

Abstract: The period between the beginning of the Early Iron Age and the end of the Archaic Period is a time of changes and developments in the Italian Peninsula, which led to the creation of regional ethnic and political groups and to the formation of the first citystates in Western Europe. In the present study, we focus on the evolution of terrestrial route network in the Tyrrhenian region of Latium vetus as it has been hypothesized by scholars from the archeological evidence. Our main goal is to investigate the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 9 publications
(8 reference statements)
1
19
0
Order By: Relevance
“…A good example of this is Iron Age Latium vetus, a region neighboring southern Etruria which we addressed in a recent study (Fulminante et al, 2017). To attain a satisfactory reproduction of the main features of empirical road network, we had to modify model EE by including a tunable amount of rich-get-richer bias.…”
Section: Beyond Straight Lines and Perfect Equality Possible Directionsmentioning
confidence: 99%
“…A good example of this is Iron Age Latium vetus, a region neighboring southern Etruria which we addressed in a recent study (Fulminante et al, 2017). To attain a satisfactory reproduction of the main features of empirical road network, we had to modify model EE by including a tunable amount of rich-get-richer bias.…”
Section: Beyond Straight Lines and Perfect Equality Possible Directionsmentioning
confidence: 99%
“…Path modelling routines in GIS are not very efficient for network (re)construction since they do not allow for simultaneously connecting multiple nodes on the basis of standardized criteria. Commonly used and effective network construction techniques limit the number of allowed connections on the basis of distance and/or the number of closest neighbours (see Gorenflo and Bell 1991;Jiménez Badillo 2004;Rivers et al 2013;Groenhuijzen and Verhagen 2017;Fulminante et al 2017). This limitation is necessary in order to prevent the creation of spurious connections, since direct links from everywhere to everywhere are not realistic.…”
Section: Network (Re)construction Techniquesmentioning
confidence: 99%
“…As far as we can tell, similar studies attempting to establish the relative importance of routes are lacking. Fulminante et al (2017), however, present a straightforward method to compare modelled networks to observed ones by taking into account the differences in network descriptors.…”
Section: Network Analysis Techniquesmentioning
confidence: 99%
“…Potential for Roman Studies: Network science has been used to explore large datasets of Roman tableware distributions (Brughmans 2010;, to study and model Roman transport systems (Graham 2006b;Isaksen 2007;Scheidel 2014;Fulminante et al 2017), to study the social networks revealed by Cicero's letters (Alexander and Danowski 1990), the spread of cults (Collar 2013), and to explore the degree of Roman imperial economic integration (Graham and Weingart 2015;Brughmans and Poblome 2016b). In these applications, the representation of Roman datasets as networks is a particularly common approach.…”
Section: Network Science Lead Author: Tom Brughmansmentioning
confidence: 99%